Rapid assessment of injection practices in Cambodia, 2002 - Goldstein Susan; Som Seiharath; Sok Srun; Perz Joseph F; Vong Sirenda; Hutin Yvan; Tulloch James (BMC, 2005)
Abstract Background Injection overuse and unsafe injection practices facilitate transmission of bloodborne pathogens such as hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV). Anecdotal reports of unsafe and unnecessary therapeutic injections and the high prevalence of HBV (8.0%), HCV (6.5%), and HIV (2.6%) infection in Cambodia have raised concern over injection safety. To estimate the magnitude and patterns of such practices, a rapid assessment of injection practices was conducted. Methods We surveyed a random sample of the general population in Takeo Province and convenience samples of prescribers and injection providers in Takeo Province and Phnom Penh city regarding injection-related knowledge, attitudes, and practices. Injection providers were observed administering injections. Data were collected using standardized methods adapted from the World Health Organization safe injection assessment guidelines. Results Among the general population sample (n = 500), the overall injection rate was 5.9 injections per person-year, with 40% of participants reporting receipt of ≥ 1 injection during the previous 6 months. Therapeutic injections, intravenous infusions, and immunizations accounted for 74%, 16% and 10% of injections, respectively. The majority (>85%) of injections were received in the private sector. All participants who recalled their last injection reported the injection was administered with a newly opened disposable syringe and needle. Prescribers (n = 60) reported that 47% of the total prescriptions they wrote included a therapeutic injection or infusion. Among injection providers (n = 60), 58% recapped the syringe after use and 13% did not dispose of the used needle and syringe appropriately. Over half (53%) of the providers reported a needlestick injury during the previous 12 months. Ninety percent of prescribers and injection providers were aware HBV, HCV, and HIV were transmitted through unsafe injection practices. Knowledge of HIV transmission through "dirty" syringes among the general population was also high (95%). Conclusion Our data suggest that Cambodia has one of the world's highest rates of overall injection usage, despite general awareness of associated infection risks. Although there was little evidence of reuse of needles and syringes, support is needed for interventions to address injection overuse, healthcare worker safety and appropriate waste disposal.